1981
DOI: 10.1080/00362178185380281
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and immune response toParacoccidioides brasiliensisin the fructivorous bat,Artibeus lituratus

Abstract: Groups of neotropical bats (Artibeus lituratus) were inoculated by the intraperitoneal or intranasal routes with varying doses of yeast phase Paracoccidioides brasiliensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Later, Greer and Bolaños () proved that the fungus did not survive in the gastrointestinal tract of A. lituratus and stated that this species probably plays no role in the distribution of P. brasiliensis in nature. In our study, both bats showed the presence of the fungus in the spleen and liver and no infection in the intestines, corroborating with previous reports (Greer & Bolaños, ; Greer & McMurray, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Later, Greer and Bolaños () proved that the fungus did not survive in the gastrointestinal tract of A. lituratus and stated that this species probably plays no role in the distribution of P. brasiliensis in nature. In our study, both bats showed the presence of the fungus in the spleen and liver and no infection in the intestines, corroborating with previous reports (Greer & Bolaños, ; Greer & McMurray, ).…”
Section: Discussionsupporting
confidence: 93%
“…Grose and Tramsitt () isolated P. brasiliensis from the intestinal tract of three frugivorous Artibeus lituratus bats. Greer and McMurray () showed that this species was susceptible to intraperitoneal and intranasal experimental infection, by observing the dissemination of the fungus to the liver and spleen and the subsequent death of the infected bats. The authors did not report the isolation of P. brasiliensis from the intestines (Greer & McMurray, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungus was isolated from internal organs as well as in bat guano-enriched soils [ 42 , 43 ]. Other closely related human fungal pathogens such as Coccidioides posadasii [ 87 ], Blastomyces dermatitidis [ 88 ], and Paracoccidioides brasiliensis [ 89 ] have been isolated only sporadically from bats. Bats are widely distributed across many continents and ecosystems, being one of the largest groups of mammals, second in number of species after the order Rodentia and first in number of individuals [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…More than 20-years ago, animal models were used to measure the immune responses in PCM, initially in hamsters [4,5], mice [6][7][8][9], and then in guinea pigs [10,11] and bats [12]. Additionally, a recent study has utilized dogs to explore certain immune functions [13].…”
Section: Introductionmentioning
confidence: 99%